Impact of psychological empowerment and perceived career support on employee work engagement with the mediating role of affective commitment - Asif Mahmood; Arooj Sahar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The ultimate plan of this study is to explore and examine the mediating influence of affective commitment while reviewing the impact of psychological empowerment and perceived career support on employee's work engagement. To test the hypotheses empirically, the regression analysis was conducted by collecting data from employees belonging to telecom sector. Our findings suggest that affective commitment partially mediates the positive effects of psychological empowerment and perceived career support in the prediction of employee work engagement. The study explored first time the mediating role of affective commitment in relationship of psychological empowerment and employees' work engagement. The study discloses practical suggestions for management of telecom sector, it also discusses the limitations of the research and it also gives direction for future studies.
Keywords: 330; psychological empowerment; perceived career support; employee work engagement; affective commitment; employee empowerment; work engagement